Improved water management is central to solving the water-energy-food trilemma in Lao PDR - McCartney, Matthew P.; Brunner, Jake (Informa UK Limited, 2021)
Relying on published literature, we reviewed water-energy-food issues in Lao PDR in the context of a policy shift to more sustainable ‘green growth’ and significantly increased infrastructure investment resulting from China’s Belt and Road Initiative. The BRI provides the prospect for the country to address its infrastructure deficit and transform from a ‘land-locked’ to a ‘land-linked’ country. However, great care is needed to ensure that future investments do not result in further environmental degradation and harm to communities. An integrated ‘nexus’ approach, in which enhanced water management is central, is a prerequisite for more inclusive and sustainable development.